A two-segment simulation model of long horse vaulting - King, M. A.; Yeadon, M. R.; Kerwin, D. G. (Journal of Sports Sciences, 1999)
The optimum pre-flight characteristics of the Hecht and handspring somersault vaults were determined using a two-segment simulation model. The model consisted of an arm segment and a body segment connected by a frictionless pin joint, simulating the vault from the Reuther board take-off through to landing. During horse contact, shoulder torque was set to zero in the model. Five independent pre-flight variables were varied over realistic ranges and an objective function was maximized to find the optimum pre-flight for each vault. The Hecht vault required a low trajectory of the mass centre during pre-flight, with a low vertical velocity of the mass centre and a low angular velocity of the body at horse contact. In contrast, the optimum handspring somersault required a high pre-flight trajectory, with a high angular velocity of the body and a high vertical velocity at horse contact. Despite the simplicity of the model, the optimum pre-flights were similar to those used in competitive performances.